Memoir of a debulked woman : enduring ovarian cancer - Gubar, Susan, 1944- (New York ; London : W.W. Norton & Co., 2012)
In this moving memoir, a renowned feminist scholar explores the physical and psychological ordeal of living with ovarian cancer.
Includes bibliographical references.
Keywords: Gubar, Susan, -- 1944- -- Health; Ovaries -- Cancer -- Patients -- United States -- Biography; Cancer -- Psychological aspects